Cytoplasmic dynein/dynactin drives kinetochore protein transport to the spindle poles and has a role in mitotic spindle checkpoint inactivation - Howell, B.J. (The Rockefeller University Press, 2001)
We discovered that many proteins located in the kinetochore outer domain, but not the inner core, are depleted from kinetochores and accumulate at spindle poles when ATP production is suppressed in PtK1 cells, and that microtubule depolymerization inhibits this process. These proteins include the microtubule motors CENP-E and cytoplasmic dynein, and proteins involved with the mitotic spindle checkpoint, Mad2, Bub1R, and the 3F3/2 phosphoantigen. Depletion of these components did not disrupt kinetochore outer domain structure or alter metaphase kinetochore microtubule number. Inhibition of dynein/dynactin activity by microinjection in prometaphase with purified p50 “dynamitin” protein or concentrated 70.1 anti-dynein antibody blocked outer domain protein transport to the spindle poles, prevented Mad2 depletion from kinetochores despite normal kinetochore microtubule numbers, reduced metaphase kinetochore tension by 40%, and induced a mitotic block at metaphase. Dynein/dynactin inhibition did not block chromosome congression to the spindle equator in prometaphase, or segregation to the poles in anaphase when the spindle checkpoint was inactivated by microinjection with Mad2 antibodies. Thus, a major function of dynein/dynactin in mitosis is in a kinetochore disassembly pathway that contributes to inactivation of the spindle checkpoint.